METHODOLOGICAL PRINCIPLES OF IMPLEMENTING CORPORATE INFOR-MATION SYSTEMS IN ENTERPRISES - Samoilenko, Antonina; Kulіk, Anna (SWorld-Ger Conference proceedings, 2024)
The article examines and characterizes the essence of corporate information management systems of the MRPII and ERP levels, their features, problems of implementing CIS at domestic enterprises and their possible solutions.